2018
DOI: 10.3390/s18103296
|View full text |Cite
|
Sign up to set email alerts
|

sEMG-Based Drawing Trace Reconstruction: A Novel Hybrid Algorithm Fusing Gene Expression Programming into Kalman Filter

Abstract: How to reconstruct drawing and handwriting traces from surface electromyography (sEMG) signals accurately has attracted a number of researchers recently. An effective algorithm is crucial to reliable reconstruction. Previously, nonlinear regression methods have been utilized successfully to some extent. In the quest to improve the accuracy of transient myoelectric signal decoding, a novel hybrid algorithm KF-GEP fusing Gene Expression Programming (GEP) into Kalman Filter (KF) framework is proposed for sEMG-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…We have developed a novel machine‐learning approach called the gene expression programming‐complex snp interactions (GEP‐CSI) data mining algorithm. This algorithm, an evolution of GEP [ 18 ], leverages linear algebra calculations to handle discrete variables and compute a fitness function score. GEP enables the exploration of an extensive solution space, pinpointing the optimal solution via a natural selection mechanism within the algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a novel machine‐learning approach called the gene expression programming‐complex snp interactions (GEP‐CSI) data mining algorithm. This algorithm, an evolution of GEP [ 18 ], leverages linear algebra calculations to handle discrete variables and compute a fitness function score. GEP enables the exploration of an extensive solution space, pinpointing the optimal solution via a natural selection mechanism within the algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Deng et al [11] combined GEP with an artificial fish swarm algorithm and found that the combination performed better than the original GEP. Yang et al [12] developed a hybrid Kalman filter GEP to reconstruct drawing and handwriting.…”
Section: Introductionmentioning
confidence: 99%